The Influence of Tax Reporting and the Core Tax System on Taxpayer Compliance (Study at the Primary Tax Service Office in DKI Jakarta) - Siagian, Panatagama; Karsam (Universitas Mohammad Husni Thamrin, 2025)
Tax revenue is one of the most significant sources of state revenue for financing national development. Therefore, taxpayer compliance is a critical focus in reforming the tax framework system in Indonesia. Digital transformation in tax administration is the government's primary strategy to improve taxpayer compliance. However, the effectiveness of digital tax reporting and the implementation of the Core Tax System still needs to be studied empirically, particularly within the Jakarta Tax Service Office (KPP). This study aims to analyze the effect of tax reporting and the Core Tax System on taxpayer compliance. The research method used is a quantitative approach with a survey technique of 101 respondents, and multiple linear regression analysis to test the partial and simultaneous effects between variables. The results show that tax reporting and the Core Tax System have a significant positive effect on taxpayer compliance, both individually and simultaneously, with an R² value of 0.522. This finding supports the theory of tax compliance and emphasizes the importance of digitizing the tax system. This study provides theoretical contributions to strengthening the fiscal compliance literature, as well as practical recommendations for tax authorities to develop a more inclusive and effective system. Further research is recommended to explore other variables such as tax morality and perceptions of fairness in the context of digitizing tax services.